Strategy of Village Owned Enterprises (Bumdes) in Increasing Village Original Income (Pades) Gresik Regency - Rahmadani Sudiarso; Isnaini Isnaini (Indonesian Journal of Cultural and Community Development, 2022)
The purpose of this study is to describe and analyze the strategy of Village Owned Enterprises (BUMDes) in Increasing Village Original Income (PADes). By using data collection techniques, namely interviews, observation and documentation as well as data analysis techniques namely descriptive qualitative carried out with the stages of data collection, data reduction, and drawing conclusions. The results of this study indicate that the BUMDes strategy in increasing Village PADes is 1) This corporate strategy (organizational strategy), sets income increase as a goal, for that BUMDes opens a savings and loan business program (cooperatives) and a trading business program and is proven to be able to increase income and in accordance with the target. 2) This program strategy (program strategy), the business program that is run has a positive impact on PADes, but has a negative impact on people who do not cooperate with BUMDes and the existence of a separate BUMDes management policy from the village government, BUMDes is more flexible in its management. 3) Resources support strategy (supporting resource strategy), BUMDes has made maximum use of supporting resources including budget, human resources, ease of obtaining information and has not made maximum use of facilities and infrastructure because it is still in the development process. 4) Institutional strategy (institutional strategy), BUMDes chooses a family way of working, leaders who free their subordinates to carry out their duties, structures formed by village heads and innovate to develop and collaborate with third parties.